Nanometer encapsulation enzyme / PBAT composite material and preparation method and application thereof

The inclusion of enzymes into PBAT through nano-encapsulated enzyme technology solves the problem of slow degradation and degradation of PBAT in industrial compost conditions, achieving faster degradation and better environmental adaptability.

CN119529486APending Publication Date: 2025-02-28SHENZHEN SYNTHETIC ERA TECH CO LTD

Patent Information

Application Number
CN202311101718.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing PBAT degradable plastics are slow to degrade under industrial composting conditions, and cannot meet the existing standards' biodegradable rate requirements, resulting in environmental pollution.

Method used

Nanocapsulation enzyme technology is used to bind the enzyme to inorganic organic nanocomposites, and nanocapsulation enzymes are prepared by coordination self-assembly method, and added to PBAT to improve its degradation performance.

Benefits of technology

The thermal stability of PBAT is improved, so that its biological activity is retained more effectively during high-temperature processing, thereby significantly accelerating the degradation rate of PBAT under various conditions such as aqueous solutions and industrial compost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529486A_ABST
    Figure CN119529486A_ABST
Patent Text Reader

Abstract

The invention discloses a PBAT (poly (butylene adipate-co-terephthalate)) composite material containing nano encapsulation enzyme as well as a preparation method and application thereof. The PBAT composite material is prepared from the following components in percentage by mass: 50 to 90 parts of PBAT resin, 0 to 40 parts of filler and 0.01 to 20 parts of nano encapsulation enzyme. The preparation method comprises the following steps: firstly synthesizing the nano encapsulation enzyme, and then mixing the nano encapsulation enzyme, the PBAT resin and the filler, extruding, and carrying out hot press molding or curtain coating and film blowing. The method is characterized in that 1) the nano encapsulated enzyme has more excellent thermal stability than other immobilized enzymes, and the biological activity of the enzyme can be effectively maintained after high-temperature heat treatment; and 2) as the biological activity of the enzyme is effectively reserved, the PBAT composite material containing the nano encapsulated enzyme has higher environmental degradation speed than pure PBAT or a PBAT composite material containing free enzyme, and the environmental degradation speed can be reflected in various conditions such as aqueous solution and industrial compost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of degradable polymer materials, and in particular to a nano-encapsulated enzyme / PBAT composite material and a preparation method and application thereof. Background Art

[0002] The full name of PBAT is polybutylene adipate terephthalate, which is made from terephthalic acid, adipic acid and 1,4-butanediol as precursors through polycondensation reaction. It is a representative biodegradable plastic. PBAT has high elongation at break, good flexibility and ductility, and mechanical properties comparable to traditional plastics (such as polyethylene PE and polyethylene terephthalate PET), and has broad application prospects in food, packaging, agriculture and other fields.

[0003] Although PBAT is a degradable plastic, in actual use, the degradation rate of PBAT is far from meeting the process requirements of existing degradation equipment. For example, under industrial composting conditions, PBAT can show biodegradable characteristics that meet the requirements within 180 days of the current national standard. However, the operating period of existing biomass treatment facilities in my country is usually 30-40 days, and the biodegradation rate of PBAT within this time range is very low, which cannot meet the requirements of the existing standards for biodegradation rate. This means that PBAT is still non-biodegradable under existing industrial composting conditions. The degradation rate of PBAT in the natural environment is even slower, and it usually takes several years to be decomposed in fresh water, sea water, soil and other environments. Therefore, even if it is a degradable plastic, if it cannot be completely and fully decomposed within a limited time, but is disposed of by incineration, landfill, etc., it will still cause damage to the environment and aggravate "white pollution."

[0004] Therefore, how to further improve the degradation rate of PBAT so that it can be decomposed faster and more fully within a limited time is an issue of key significance and value.

[0005] A feasible idea is to add some biological entities (i.e., enzymes) that have degradation activity on plastics to plastics to prepare composite materials to improve their degradation performance. Patents CN104159950B, CN106519266B, CN107835829B, etc. all disclose methods of blending enzymes with degradable plastics to increase their degradation rate. However, in these disclosed methods, there are still two problems. One is that the thermal stability of the enzyme is poor. The high temperature environment of plastic processing will destroy the spatial structure of the enzyme, greatly reducing its biological activity, which is not enough to give full play to the degradation effect of the enzyme; the second is that this method still lacks the evaluation of degradation effects in actual application scenarios, such as tests in industrial composting.

[0006] Therefore, in this patent, we propose a composite material of PBAT containing nano-encapsulated enzyme and a preparation method thereof. By adding an enzyme activity protectant, the thermal stability of the nano-encapsulated enzyme can be further improved, so that its biological activity during high-temperature processing can be more effectively retained, so that the composite material has better degradation performance than pure PBAT and PBAT containing free enzymes or other immobilized enzymes. At the same time, it also proves that our method has the effect of accelerating the degradation of PBAT under industrial composting conditions. Summary of the invention

[0007] Based on this, the purpose of the present invention is to provide a PBAT composite material containing nano-encapsulated enzymes and a preparation method and application thereof.

[0008] In one aspect, the present invention provides a PBAT composite material containing nano-encapsulated enzyme.

[0009] Furthermore, the PBAT composite material is prepared from the following components in percentage by mass: 50-90 parts of PBAT resin, 0-40 parts of filler, and 0.01-20 parts of nano-encapsulated enzyme.

[0010] Furthermore, the amount of PBAT resin is 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, and 90 parts.

[0011] Furthermore, the nano-encapsulated enzyme is an enzyme-inorganic and organic nanocomposite.

[0012] Furthermore, the nano-encapsulated enzyme is a porous material assembled by inorganic components and organic ligands through coordination, and enzymes and enzyme activity protectors are added during the preparation process.

[0013] The macroscopic shape of the nano-encapsulated enzyme is a powdery solid, and the microscopic structure is a porous microsphere or polyhedral nanoparticle with a particle size distribution of 10-5000 nm. Preferably, the particle size is 10-500 nm, more preferably 10-100 nm.

[0014] The nano-encapsulated enzyme contains one or more inorganic metal elements, wherein the content of the metal elements is 5-60wt%, preferably 5wt%, 8wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 60wt%. The metal elements are any one or more of Fe, Co, Cr, Ca, Ni, Zn, Mn, Cu, and Ag.

[0015] The enzyme content in the nano-encapsulated enzyme is 0.1-90wt%, preferably 0.5wt%, 1wt%, 2wt%, 3wt%, 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 20wt%, 25wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt%, more preferably 5wt%-30wt%. The enzyme is selected from any one or more of cutinase, lipase, and esterase having PBAT degradation activity, but is not limited thereto.

[0016] Furthermore, the composite material contains at least one filler selected from one or more of modified starch, cellulose, lignin, wood powder, bamboo powder, glass fiber, carbon fiber, calcium carbonate, calcium phosphate, barium sulfate, magnesium sulfate, talc, kaolin, and wollastonite.

[0017] Further, the amount of the filler is 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts. Further, the amount of the filler is 1-40 parts, for example, 5-35 parts, and also for example, 20-30 parts.

[0018] Furthermore, the nano-encapsulated enzyme contains at least one enzyme activity protective agent for improving the thermal stability of the nano-encapsulated enzyme. The enzyme activity protective agent includes at least one of an electrostatic modifier and a chemical cross-linking agent. Furthermore, the enzyme activity protective agent consists of an electrostatic modifier and a chemical cross-linking agent, and the synergistic effect of the two can significantly improve the protein protective activity. In the present invention, the enzyme activity protection method of electrostatic modification + chemical cross-linking makes full use of the properties of amino acids, polymers, polyphenols and other substances such as charge, functional groups, and reactivity to enhance the interaction between enzymes and between enzymes and encapsulation carriers, so that the nano-encapsulated enzyme has more outstanding stability.

[0019] In the present invention, the method for synthesizing nano-encapsulated enzyme is to obtain the enzyme by coordination self-assembly of inorganic components, organic ligands, enzymes and enzyme activity protective agents in a solvent. The enzyme is encapsulated in the interior or pores of the metal ions and organic ligands during the coordination assembly process; the enzyme activity protective agent enhances the interaction between enzymes and between enzymes and encapsulation carriers, thereby making the nano-encapsulated enzyme have more outstanding stability.

[0020] In the present invention, the inorganic component is selected from metal salts, specifically selected from one or more salts of Fe, Co, Cr, Ca, Ni, Zn, Mn, Cu, and Ag; the anion of the salt may be one or more of halide ions, sulfate ions, hydrogen sulfate ions, nitrate ions, and acetate ions. Preferably, the salt is a water-soluble metal salt, for example, one or more of cobalt nitrate, cobalt chloride, zinc nitrate, zinc acetate, ferric chloride, calcium chloride, chromium chloride, copper nitrate, manganese chloride, and silver nitrate, including anhydrous forms and hydrate forms thereof, but not limited thereto.

[0021] In the present invention, the organic ligand is a multifunctional compound, preferably, at least one of 2,2'-bipyridine, 4,4'-bipyridine, 2-methylimidazole, 4-methylimidazole, 1-methylimidazole, benzimidazole, 1,4-terephthalic acid, 1,3,5-benzenetricarboxylic acid, 2,6-naphthalene dicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, but not limited thereto.

[0022] In the present invention, the molar ratio of metal ions to organic ligands in the inorganic component is 1:0.01-100, preferably 1:0.1, 1:1, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:50, 1:100, and more preferably 1:5-50.

[0023] In the present invention, the electrostatic modifier is any one or more of polyethylene glycol, polyvinyl pyrrolidone, polyglutamic acid, polyaspartic acid, polylysine, branched polyethyleneimine, Pluronic F-127, and cysteine. The electrostatic modifier can perform surface modification on biomacromolecules such as enzymes, and enhance the repulsion between molecules by modifying their surface charge, thereby improving their stability.

[0024] In the present invention, the chemical crosslinking agent is any one or more of polyphenolic compounds such as dopamine, tannic acid, and gallic acid. The chemical crosslinking agent can undergo oxidative self-polymerization under weak alkaline conditions to form a coating on the surface of the material, and can also react with the amino groups on the surface of the enzyme to form covalent crosslinks, thereby improving the stability of the enzyme.

[0025] In the present invention, the mass ratio of the electrostatic modifier to the enzyme is 1-100:100-1, preferably 1-100:100, specifically 1:100, 10:100, 20:100, 30:100, 40:100, 50:100, 60:100, 70:100, 80:100, 90:100, 100:100, and more preferably 20-50:100. Preferably, the mass ratio of the chemical cross-linking agent to the enzyme is 1-100:100-1, preferably 1-100:100, specifically 1:100, 10:100, 20:100, 30:100, 40:100, 50:100, 60:100, 70:100, 80:100, 90:100, 100:100, more preferably 20-50:100.

[0026] In the present invention, the ratio of the enzyme to the metal ions in the inorganic component is 1-1000 mg:1 mmol, preferably 1 mg:1 mmol, 10 mg:1 mmol, 50 mg:1 mmol, 100 mg:1 mmol, 200 mg:1 mmol, 300 mg:1 mmol, 400 mg:1 mmol, 500 mg:1 mmol, 1000 mg:1 mmol, and more preferably 10-300 mg:1 mmol.

[0027] In the present invention, the solvent and the solvent in the solvent are selected from at least one of water, methanol, ethanol and ammonia water.

[0028] In the present invention, the temperature of the coordination self-assembly reaction is 0-40° C., preferably at room temperature; the reaction time is 0.1-48 h, preferably 0.5-2 h.

[0029] Furthermore, the amount of nano-encapsulated enzyme in the composite material is 0.01 parts, 0.05 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.5 parts, 2 parts, 3 parts, 5 parts, 10 parts, 15 parts, and 20 parts.

[0030] On the other hand, the present invention provides a method for preparing a PBAT composite material containing nano-encapsulated enzymes, comprising the following steps: mixing the nano-encapsulated enzymes with PBAT and an optional filler to obtain a premix, and then adding the premix to a twin-screw extruder for blending, extrusion, and granulation to obtain a PBAT composite material containing nano-encapsulated enzymes.

[0031] Furthermore, the composite material can be further processed by processes such as casting, film blowing, hot pressing, etc. to obtain products of different forms. The products include agricultural mulch films, food packaging, plastic bags, etc.

[0032] In the present invention, the processing temperature of the twin-screw extruder is 80-260°C, preferably 80°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 175°C, 180°C, 185°C, 190°C, 200°C, 220°C, more preferably 170-190°C; the processing time is 1-20min, preferably 1min, 2min, 5min, 10min, 15min, 20min, more preferably 1-10min.

[0033] The present invention provides a PBAT composite material containing nano-encapsulated enzyme prepared by the above-mentioned preparation method.

[0034] The present invention also provides a degradable plastic product made from the PBAT composite material as a raw material.

[0035] The present invention also provides the application of the degradable plastic product in the fields of agricultural mulch film, food packaging, plastic bags, etc.

[0036] The full name of PBS is polybutylene succinate, which has a very similar chemical composition and chain structure to PBAT. Therefore, its mechanical, crystallization, processing, biodegradation and other properties are very close to those of PBAT.

[0037] Based on this, the present invention also provides a PBS composite material containing nano-encapsulated enzymes, characterized in that it is prepared from the following components in mass percentage, including 50-90 parts of PBS resin, 0-40 parts of filler, and 0.01-20 parts of nano-encapsulated enzymes. The composition and preparation method of the nano-encapsulated enzymes are as described above.

[0038] The filler is selected from one or more of modified starch, cellulose, lignin, wood powder, bamboo powder, glass fiber, carbon fiber, calcium carbonate, calcium phosphate, barium sulfate, magnesium sulfate, talc, kaolin, and wollastonite.

[0039] Compared with the prior art, the present invention has the following advantages and applications:

[0040] (1) The nanoencapsulated enzyme provided by the present invention has better thermal stability than free enzymes or other immobilized enzymes, and can effectively retain its biological activity, i.e., its degradation activity on PBAT, during the high temperature process of PBAT processing;

[0041] (2) On this basis, the PBAT composite material containing nano-encapsulated enzymes obtained in the present invention has a faster environmental degradation rate than pure PBAT or PBAT composite materials containing free enzymes or other immobilized enzymes, which can be reflected in various conditions such as aqueous solution and industrial composting. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1This is a scanning electron microscope photo of the nanoencapsulated enzyme of Example 1

[0043] Figure 2 Comparison of the composting degradation performance of the nanoencapsulated enzyme / PBAT composite material of Example 5 and the natural enzyme / PBAT composite material of Comparative Example 1 (calculation of biodegradation rate)

[0044] Figure 3 Comparison of the composting degradation performance of the nanoencapsulated enzyme / PBAT composite material of Example 5 and the natural enzyme / PBAT composite material of Comparative Example 1 (calculation of relative biodegradation rate) DETAILED DESCRIPTION

[0045] The present invention is described in more detail hereinafter to facilitate understanding of the present invention.

[0046] It should be understood that the terms or words used in the specification and claims should not be understood as having the meaning defined in the dictionary, but should be understood as having the meaning consistent with their meaning in the context of the present invention based on the following principle: the concept of the term can be appropriately defined by the inventor for the best explanation of the present invention.

[0047] Example 1

[0048] This embodiment prepares nano-encapsulated enzyme in aqueous solution, comprising the following steps:

[0049] (1) preparing 10 mL of a 1.0 mol / L 1-methylimidazole aqueous solution, 10 mL of a 0.1 mol / L zinc nitrate aqueous solution, 1 mL of a 40 mg / mL polyvinylpyrrolidone (PVP) aqueous solution, 1 mL of a 40 mg / mL tannic acid (TA) aqueous solution, and 1 mL of a 100 mg / mL cutinase aqueous solution, respectively, and completely dissolving them at room temperature to obtain a uniform solution;

[0050] (2) mixing the solutions prepared in step (1) in a glass reactor, and stirring at room temperature using a magnetic stirrer at a speed of 500 rpm for 30 min;

[0051] (3) centrifuging the solution obtained in step (2) at 15,000 rpm for 5 min to obtain a precipitate, removing the supernatant, resuspending the precipitate with deionized water, and repeating the washing twice;

[0052] (4) The precipitate obtained in step (3) was pre-frozen at -20°C for 12 hours and freeze-dried for 24 hours to obtain the nanoencapsulated enzyme.

[0053] Among them, PVP and TA, as protein active protective agents, have electrostatic modification and chemical cross-linking effects on enzymes, respectively, and are used to enhance the interaction in nanoencapsulated enzymes and improve the thermal stability of nanoencapsulated enzymes. The microscopic morphology of nanoencapsulated enzymes was observed using a scanning electron microscope (see Figure 1 ), whose microstructure is uniformly distributed spherical nanoparticles with an average particle size of 22nm.

[0054] In this embodiment, the loading rate of the enzyme in the nano-encapsulated enzyme is 9.3 wt %.

[0055] The enzyme loading rate refers to the mass of enzyme contained in the unit mass of the complex, expressed in wt%, and can be calculated according to the following formula:

[0056] Enzyme loading rate = (amount of added enzyme - amount of enzyme in supernatant and washing solution) / mass of obtained complex × 100%.

[0057] Example 2

[0058] This example prepares nano-encapsulated enzyme in aqueous solution. Compared with Example 1, the example does not contain a protein activity protective agent with electrostatic modification effect, and includes the following steps:

[0059] (1) preparing 10 mL of a 1.0 mol / L 1-methylimidazole aqueous solution, 10 mL of a 0.1 mol / L zinc nitrate aqueous solution, 1 mL of an 80 mg / mL tannic acid (TA) aqueous solution, and 1 mL of a 100 mg / mL cutinase aqueous solution, respectively, and completely dissolving them at room temperature to obtain a uniform solution;

[0060] (2) mixing the solutions prepared in step (1) in a glass reactor, and stirring at room temperature using a magnetic stirrer at a speed of 500 rpm for 30 min;

[0061] (3) centrifuging the solution obtained in step (2) at 15,000 rpm for 5 min to obtain a precipitate, removing the supernatant, resuspending the precipitate with deionized water, and repeating the washing twice;

[0062] (4) The precipitate obtained in step (3) was pre-frozen at -20°C for 12 hours and freeze-dried for 24 hours to obtain the nanoencapsulated enzyme.

[0063] In this embodiment, the loading rate of the enzyme in the nano-encapsulated enzyme is 8.6 wt %.

[0064] Example 3

[0065] This embodiment prepares nano-encapsulated enzyme in aqueous solution, and compared with Example 1, does not contain a protein activity protective agent with chemical cross-linking effect, and includes the following steps:

[0066] (1) preparing 10 mL of a 1.0 mol / L 1-methylimidazole aqueous solution, 10 mL of a 0.1 mol / L zinc nitrate aqueous solution, 1 mL of an 80 mg / mL polyvinylpyrrolidone (PVP) aqueous solution, and 1 mL of a 100 mg / mL cutinase aqueous solution, respectively, and completely dissolving them at room temperature to obtain a uniform solution;

[0067] (2) mixing the solutions prepared in step (1) in a glass reactor, and stirring at room temperature using a magnetic stirrer at a speed of 500 rpm for 30 min;

[0068] (3) centrifuging the solution obtained in step (2) at 15,000 rpm for 5 min to obtain a precipitate, removing the supernatant, resuspending the precipitate with deionized water, and repeating the washing twice;

[0069] (4) The precipitate obtained in step (3) was pre-frozen at -20°C for 12 hours and freeze-dried for 24 hours to obtain the nanoencapsulated enzyme.

[0070] In this embodiment, the loading rate of the enzyme in the nano-encapsulated enzyme is 8 wt %.

[0071] Example 4

[0072] This example prepares nanoencapsulated enzymes in aqueous solution, and compared with Example 1, does not contain any protein activity protective agent, and includes the following steps:

[0073] (1) preparing 10 mL of a 1.0 mol / L 1-methylimidazole aqueous solution, 10 mL of a 0.1 mol / L zinc nitrate aqueous solution, and 1 mL of a 100 mg / mL cutinase aqueous solution, respectively, and completely dissolving them at room temperature to obtain a uniform solution;

[0074] (2) mixing the solutions prepared in step (1) in a glass reactor, and stirring at room temperature using a magnetic stirrer at a speed of 500 rpm for 30 min;

[0075] (3) centrifuging the solution obtained in step (2) at 15,000 rpm for 5 min to obtain a precipitate, removing the supernatant, resuspending the precipitate with deionized water, and repeating the washing twice;

[0076] (4) The precipitate obtained in step (3) was pre-frozen at -20°C for 12 hours and freeze-dried for 24 hours to obtain the nanoencapsulated enzyme.

[0077] In this embodiment, the loading rate of the enzyme in the nano-encapsulated enzyme is 11.2 wt %.

[0078] The enzymatic activity of the nanoencapsulated enzyme is measured by UV-visible spectrophotometer, comprising the following steps:

[0079] (1) Weigh 5 mg of nanoencapsulated enzyme and add it to 1 mL of Tris-HCl buffer (80 mM, pH = 7) containing 100 mM EDTA, and stir it with a magnetic stirrer at 500 rpm for 30 min;

[0080] (2) centrifuging the solution obtained in step (2) at 15,000 rpm for 5 min, and retaining the supernatant as the enzyme solution to be tested;

[0081] (3) 2 μL of p-nitrophenol butyrate was dissolved in 1 mL of acetone, and then added dropwise into 20 mL of phosphate buffer (50 mM, pH = 7) under magnetic stirring, and continued to stir at 25°C for 5 min to obtain an active substrate solution;

[0082] (4) In a typical activity detection system, 100 μL of the enzyme solution to be tested is added to 900 μL of the typical substrate solution described above, and the absorbance at 348 nm in the reaction system is detected over time. The specific enzyme solution concentration and detection time are appropriately adjusted according to the different enzyme activities of the sample to ensure that the absorbance is within the linear range.

[0083] (5) Enzyme activity can be calculated by the following formula:

[0084] Enzyme activity = (ΔAbs / Δt) / concentration of the enzyme solution to be tested. The thermal stability of the nanoencapsulated enzyme was determined using a small hot press, including the following steps:

[0085] (1) Weigh 10 mg of nanoencapsulated enzyme, place it on a 30 cm × 30 cm stainless steel sheet, and cover it with aluminum foil;

[0086] (2) placing a stainless steel sheet covered with aluminum foil between the upper and lower hot pressing plates of a hot press, pressing the plates together, and heating at a certain temperature for different periods of time;

[0087] (3) Release the pressure, remove the stainless steel sheet from between the upper and lower heating plates, tear off the covering aluminum foil, recover the nano-encapsulated enzyme, and measure the enzyme activity according to the above method.

[0088] The residual enzyme activity results of each sample after heating at 180°C are shown in Table 1 below, where the residual enzyme activity represents the ratio of the activity of the sample to be tested before and after heating according to the aforementioned activity testing method, i.e., activity after heating / activity before heating × 100%. Among them, the method for testing the activity of the natural enzyme is to directly prepare a certain concentration of the enzyme solution to be tested in 1 mL of Tris-HCl buffer (80 mM, pH = 7) containing 100 mM EDTA, and the rest is the same as the aforementioned method for testing the activity of the nanoencapsulated enzyme.

[0089] Table 1 Thermal stability of nanoencapsulated enzymes at 180°C

[0090]

[0091] Through Table 1 and Figure 1 The data show that compared with natural enzymes, nanoencapsulated enzymes have better thermal stability. At the same time, the addition of enzyme activity protectors is crucial to the thermal stability of nanoencapsulated enzymes, which can help the enzymes withstand high temperature environments and effectively retain their activity. The simultaneous use of chemical cross-linkers and electrostatic modifiers produces a synergistic effect, further increasing the enzyme's ability to withstand high temperature environments, and the retained activity is significantly improved.

[0092] Example 5

[0093] In this example, a PBAT composite material containing nano-encapsulated enzymes was prepared according to the following method, including the following steps, wherein the nano-encapsulated enzymes were prepared according to the method described in Example 1:

[0094] (1) According to the following formula, each raw material (by mass) was measured and physically mixed to obtain a premix: 69.3 parts of PBAT, 29.7 parts of thermoplastic starch, and 1 part of nanoencapsulated enzyme;

[0095] (2) adding the premix into a twin-screw extruder, controlling the screw temperature at 160-180° C., and adjusting the screw speed so that the residence time of the material in the extruder is 10 min;

[0096] (3) After the material at the outlet of the extruder is cooled and pelletized, a PBAT composite material with an addition amount of about 1 wt% of nano-encapsulated enzyme is obtained.

[0097] Example 6

[0098] In this example, a PBAT composite material containing nano-encapsulated enzymes was prepared according to the following method, including the following steps, wherein the nano-encapsulated enzymes were prepared according to the method described in Example 1:

[0099] (1) According to the following formula, each raw material (by mass) was measured and physically mixed to obtain a premix: 69.6 parts of PBAT, 29.9 parts of thermoplastic starch, and 0.5 parts of nanoencapsulated enzyme;

[0100] (2) adding the premix into a twin-screw extruder, controlling the screw temperature at 160-180° C., and adjusting the screw speed so that the residence time of the material in the extruder is 10 min;

[0101] (3) After the material at the outlet of the extruder is cooled and pelletized, a PBAT composite material with an addition amount of about 0.5 wt% of nano-encapsulated enzyme is obtained.

[0102] Example 7

[0103] In this example, a PBAT composite material containing nano-encapsulated enzymes was prepared according to the following method, including the following steps, wherein the nano-encapsulated enzymes were prepared according to the method described in Example 1:

[0104] (1) According to the following formula, each raw material (by mass) was measured and physically mixed to obtain a premix: 69.9 parts of PBAT, 30 parts of thermoplastic starch, and 0.1 parts of nanoencapsulated enzyme;

[0105] (2) adding the premix into a twin-screw extruder, controlling the screw temperature at 160-180° C., and adjusting the screw speed so that the residence time of the material in the extruder is 10 min;

[0106] (3) After the material at the outlet of the extruder is cooled and pelletized, a PBAT composite material with an addition amount of about 0.1 wt% of nano-encapsulated enzyme is obtained.

[0107] Comparative Example 1

[0108] In this comparative example, a PBAT composite material containing natural enzymes was prepared according to the following method, comprising the following steps:

[0109] (1) According to the following formula, each raw material (by mass) was measured and physically mixed to obtain a premix: 70 parts of PBAT, 30 parts of thermoplastic starch, and natural enzyme powder having the same enzyme equivalent as 1 part of nanoencapsulated enzyme;

[0110] (2) adding the premix into a twin-screw extruder, controlling the screw temperature at 160-180° C., and adjusting the screw speed so that the residence time of the material in the extruder is 10 min;

[0111] (3) After the material at the outlet of the extruder is cooled and pelletized, a PBAT composite material having the same enzyme equivalent as the PBAT material containing about 1 wt% nano-encapsulated enzyme is obtained.

[0112] Comparative Example 2

[0113] In this comparative example, a PBAT material without an enzyme is prepared according to the following method, comprising the following steps:

[0114] (1) According to the following formula, each raw material (by mass) was measured and physically mixed to obtain a premix: 70 parts of PBAT and 30 parts of thermoplastic starch;

[0115] (2) adding the premix into a twin-screw extruder, controlling the screw temperature at 160-180° C., and adjusting the screw speed so that the residence time of the material in the extruder is 10 min;

[0116] (3) The material at the outlet of the extruder is cooled and pelletized to obtain a PBAT composite material without enzyme.

[0117] Test Example 1

[0118] Method for evaluating the degradation performance of PBAT materials in solution:

[0119] First, the PBAT masterbatch is processed into thin sheets by hot pressing, and then cut into discs as test samples. Then the test samples are completely immersed in the degradation solution, which can be tap water, deionized water, or a buffer solution with a certain concentration and pH. The degradation process is carried out at a constant temperature, and after a specified period of time, the solution degradation performance of the material is evaluated by calculating the mass loss of the test sample.

[0120] The mass loss of the sample is calculated according to the following formula:

[0121] Δm=(m0-m t ) / m0×100%

[0122] Where m0 represents the initial mass of the sample, m t Represents the final mass of the sample after a specified degradation time t.

[0123] Table 2 Degradation performance of PBAT composite materials in solution

[0124]

[0125] Note: Degradation conditions are 50°C, phosphate buffer (100mM, pH=7)

[0126] From the experimental data in Table 2, it can be found that the PBAT composite material containing nano-encapsulated enzyme has a faster solution degradation performance than pure PBAT and PBAT containing enzyme (same enzyme equivalent) composite material, indicating that compared with natural enzymes, the nano-encapsulated enzyme in the present invention can more effectively retain the biological activity of the enzyme during the high temperature processing of PBAT, thereby promoting the degradation of PBAT in solution.

[0127] Test Example 2

[0128] Methods for evaluating the degradation performance of PBAT materials in industrial composting:

[0129] The standard GB / T 19277.1-2011 describes the method for evaluating the degradation performance of materials under controlled composting conditions, that is, evaluating the aerobic biodegradability of materials by measuring the carbon dioxide released. The standard GB / T41010-2021 sets requirements for the biodegradation rate of biodegradable plastics and their products, that is, the relative biodegradation rate should be greater than or equal to 90%, and the absolute biodegradation rate should be greater than 60%, and stipulates that the biodegradation test under industrial composting conditions should be carried out in accordance with the method specified in GB / T19277.1-2011.

[0130] Therefore, in the present invention, the composting degradation performance of the nanoencapsulated enzyme / PBAT composite material was evaluated according to the method specified in GB / T 19277.1-2011. The composting degradation test results of Example 5 and Comparative Example 1 are shown in Figure 2 , Figure 3 It can be found that the composting degradation rate of the nano-encapsulated enzyme / PBAT composite material is significantly faster than that of the enzyme / PBAT composite material, which further proves the better thermal stability of the nano-encapsulated enzyme.

[0131] The above describes the preferred embodiments of the present invention, but it is not intended to limit the present invention. Those skilled in the art may make improvements and changes to the embodiments disclosed herein without departing from the scope and spirit of the present invention.

Claims

1. A PBAT composite material containing nano-encapsulated enzymes, characterized in that: The invention is prepared from the following components in the following mass percentages, including 50-90 parts of PBAT resin, 0-40 parts of filler, and 0.01-20 parts of nano-encapsulated enzyme.

2. The PBAT composite material according to claim 1, characterized in that: The nanoencapsulated enzyme is an enzyme-inorganic organic nanocomposite, which is a powdered solid in macroscopic properties and a porous microsphere or polyhedral nanoparticle with a particle size distribution of 10-5000 nm in microscopic structure. It contains one or more inorganic metal elements, wherein the metal element content is 5-60wt%, and the enzyme content is 0.1-90wt%. The metal element is any one or more of Fe, Co, Cr, Ca, Ni, Zn, Mn, Cu, and Ag, and the enzyme is selected from any one or more of cutinase, lipase, and esterase having PBAT degradation activity.

3. The PBAT composite material according to claim 1, characterized in that: The nano-encapsulated enzyme is a porous material assembled by inorganic components and organic ligands through coordination, and enzymes and enzyme activity protectors are added during the preparation process.

4. The PBAT composite material according to claim 3, characterized in that: The method for synthesizing nano-encapsulated enzymes is to obtain them by coordination self-assembly of inorganic components, organic ligands, enzymes and enzyme activity protectors in a solvent.

5. The PBAT composite material according to claim 3 or 4, characterized in that: The inorganic component is selected from metal salts, specifically any one or more of salts of Fe, Co, Cr, Ca, Ni, Zn, Mn, Cu, and Ag; the organic ligand is a multifunctional compound, which is any one or more of 2,2'-bipyridine, 4,4'-bipyridine, 2-methylimidazole, 4-methylimidazole, 1-methylimidazole, benzimidazole, 1,4-terephthalic acid, 1,3,5-benzenetricarboxylic acid, 2,6-naphthalene dicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, and butenedioic acid; the electrostatic modifier is any one or more of polyethylene glycol, polyvinyl pyrrolidone, polyglutamic acid, polyaspartic acid, polylysine, branched polyethylene imine, Pluronic F-127, and cysteine; the chemical crosslinking agent is any one or more of polyphenol compounds such as dopamine, tannic acid, and gallic acid.

6. The PBAT composite material according to claim 1, characterized in that: The composite material contains at least one filler selected from one or more of modified starch, cellulose, lignin, wood powder, bamboo powder, glass fiber, carbon fiber, calcium carbonate, calcium phosphate, barium sulfate, magnesium sulfate, talc, kaolin, and wollastonite.

7. The method for preparing the PBAT composite material according to claim 1, characterized in that: The nano-encapsulated enzyme is mixed with PBAT and filler to obtain a premix, and then the premix is ​​added to an extruder for extrusion granulation to obtain a PBAT composite material.

8. The method for preparing the PBAT composite material according to claim 7, characterized in that: The processing temperature of the extruder is 80-260° C., and the processing time is 1-20 min.

9. A degradable plastic product, characterized in that: The PBAT composite material containing nano-encapsulated enzymes as described in any one of claims 1 to 6 is used as a raw material.

10. Application of the degradable plastic product according to claim 9 in the fields of agricultural mulch, food packaging, plastic bags, etc.

11. A PBS composite material containing nano-encapsulated enzymes, characterized in that: The invention is prepared from the following components in the following mass percentages, including 50-90 parts of PBS resin, 0-40 parts of filler and 0.01-20 parts of nano-encapsulated enzyme.

Citation Information

Patent Citations

  • Preparation method of polymer / biological entity alloy

    CN104159950B

  • Preparation method of polymer / bio-entity alloy

    CN106519266B

  • Masterbatch composition containing high concentration of biological entities

    CN107835829B

Cited By

  • High-strength high-barrier degradable plastic packaging film and preparation method thereof

    CN120682612A

  • High-strength high-barrier degradable plastic packaging film and preparation method thereof

    CN120682612B

  • Biomass composite decorative paper based on nanocellulose enhancement and preparation method thereof

    CN121321443A

  • A biomass composite decorative paper reinforced with nanocellulose and its preparation method

    CN121321443B